Business consulting para la empresa CONAUTO - Salazar Torres, Karina Carmen (2024)
Currently, CONAUTO faces the challenge of improving its vehicle delivery times to meet the increasingly high expectations of its customers. An on-time delivery compliance index (TE%) below the optimum generates dissatisfaction, damages the company's image, and limits its growth potential. To overcome this challenge, CONAUTO has designed a plan that contemplates the implementation of innovative and effective measures: (a) Expansion of service capacity: The capacity of the maintenance service area will be increased by 50%, going from 14 to 21 modules. This will allow for servicing 64 vehicles per day, 49% more than the current 43, significantly reducing the average service time per vehicle from 2.8 to 1.7 hours, (b) Implementation of cutting-edge technology: The "16-cell Rotary Parking System" will be incorporated, a revolutionary technology that will streamline vehicle delivery and distribution processes, reducing waiting times and increasing efficiency by 20%, and (c) Strengthening of human capital: The number of trained workers will be increased by 20%, ensuring highly qualified personnel committed to service excellence. The implementation of this plan will generate a series of tangible benefits for CONAUTO: (a) Reduction of average service time per vehicle: It will decrease from 2.8 to 1.7 hours, improving efficiency and customer satisfaction, (b) Elevation of the on-time delivery compliance index (TE%): It will exceed 95%, strengthening CONAUTO's image as a reliable company committed to its customers, (c) 5% growth in after-sales service revenue: An increase in customer satisfaction will drive demand for these services, generating greater profitability, and (d) 5% improvement in the customer satisfaction index (CSI): This will consolidate customer loyalty and position CONAUTO as a leader in customer service excellence. iv The total investment for the project is S/ 804,479.15 and includes the "Rotary Parking System". It has been rigorously evaluated and determined to be economically viable: (a) Net Present Value (NPV): S/ 553,072.08 (positive), indicating that the project will generate value for the company by exceeding the initial investment, (b) Internal Rate of Return (IRR): 52%, higher than the cost of capital opportunity (COK) of 7%, evidencing the project's profitability, and (c) Investment Recovery Period (IRP): 1 year and 3 months, demonstrating the rapid recovery of the investment. The implementation of the proposed plan represents an unbeatable opportunity for CONAUTO to take a leap towards excellence in customer service. The tangible benefits in efficiency, customer satisfaction, profitability, and market positioning, coupled with the economic viability of the project, make it a fundamental decision for CONAUTO's future.